ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИДА ТАЛАБАЛАРНИ КРЕДИТ – МОДУЛ ТИЗИМИДА ЎҚИТИШНИНГ НАЗАРИЙ АСОСЛАРИ - Жалолова, П.М. (SCIENCE and SOCIETY, 2021)
This article provides scientific and theoretical information about the credit-module system introduced in the higher education system and its requirements and opportunities. The purpose, advantages, peculiarities of the credit-module system and the methodology of evaluation in this system are described. There is information about the types of credit-module systems available in the world.